Indonesian EFL Students’ Trust: English Teachers Educators’ VS Educational Influencers - Salsabila, Revanda Putri; Abid, Nuskhan (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the factors influencing Indonesian EFL Islamic University students' preference for educational influencers over their teacher educators. While social media has emerged as a significant source of information, there is a limited understanding of why students trust online influencers more than their formally qualified lecturers. The purpose of this study is to analyze and identify the specific reasons behind this comparative trust. Using qualitative interviews with five EFL students, data was collected via WhatsApp and analyzed through reduction, presentation, and verification. The findings reveal four main factors: (1) engaging and visually appealing video content, (2) relevance of topics to daily life, (3) entertaining and interactive teaching methods, and (4) perceived credibility enhanced by social media following. These results highlight the need for traditional educators to adapt teaching styles and integrate digital tools to better meet students' current learning preferences.